Pluralism of competition policy paradigms and the call for regulatory diversity - Oliver Budzinski (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2003)
Contrary to some contemporary arguing, competition economics are characterized by a considerable pluralism of theories and policy paradigms. This includes deviating views on core concepts like the nature of competition, the meaning of efficiency, or the goal of antitrust. The paper demonstrates the incompatibilities of different economic competition theories and policy programs. It argues that this pluralism of concepts is both empirically sustainable and theoretically beneficial for future scientific progress. Therefore, no ultimate competition theory can ever be expected. This has to be considered when competition policy systems are designed, especially on the international level. A minimum of decentralization is necessary to maintain regulatory diversity which keeps the system open for theory innovation and changes in business environment.
Keywords: L40; H77; B52; L10; 330; regulatory diversity; institutional federalism; competition policy paradigms; industrial economics; centralism and decentralism; law and economics; methodology of science; Wettbewerbspolitik; Wettbewerbstheorie; Regulierung; Dogmengeschichte; Institutioneller Wettbewerb; Theorie; Welt